2018
DOI: 10.1007/s11128-018-2059-7
|View full text |Cite
|
Sign up to set email alerts
|

Verifiable threshold quantum secret sharing with sequential communication

Abstract: A (t, n) threshold quantum secret sharing (QSS) is proposed based on a single d-level quantum system. It enables the (t, n) threshold structure based on Shamir's secret sharing and simply requires sequential communication in d-level quantum system to recover secret. Besides, the scheme provides a verification mechanism which employs an additional qudit to detect cheats and eavesdropping during secret reconstruction, and allows a participant to use the share repeatedly. Analyses show that the proposed scheme is… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
25
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 25 publications
(25 citation statements)
references
References 45 publications
(89 reference statements)
0
25
0
Order By: Relevance
“…In this section, let us give a brief description of the verifiable (t, n) threshold quantum secret sharing scheme with sequential communication [22], which includes both the classical private share distribution phase and the secret sharing phase. Moreover, a dealer Alice and n agents Bob 1 , Bob 2 , .…”
Section: Verifiable Threshold Quantum Secret Sharing Scheme With mentioning
confidence: 99%
See 3 more Smart Citations
“…In this section, let us give a brief description of the verifiable (t, n) threshold quantum secret sharing scheme with sequential communication [22], which includes both the classical private share distribution phase and the secret sharing phase. Moreover, a dealer Alice and n agents Bob 1 , Bob 2 , .…”
Section: Verifiable Threshold Quantum Secret Sharing Scheme With mentioning
confidence: 99%
“…To better understand the verifiable threshold quantum secret sharing scheme and its cryptanalysis, a simple introduction on the cyclic property of mutually unbiased bases (MUBs) is firstly given [15]. It has been shown that if d is an odd prime, then there are [22], where…”
Section: Cryptanalysis Of Verifiable Threshold Quantum Secret Shmentioning
confidence: 99%
See 2 more Smart Citations
“…The dealer distributes a secret message s to n participants which at least t ≤ n participants combine to recover the secret. It is known as a (t, n)-threshold scheme [2][3][4][5][6][7][8][9]. Quantum secret sharing (QSS) is an extension of classical secret sharing via quantum states.…”
Section: Introductionmentioning
confidence: 99%